Multidimensional bioinformatics perspective on smoking-linked driver genes and immune regulatory mechanisms in non-small cell lung cancer - Can Ouyang; Xiaopeng Yu; Huazhong Wang; Puhua Zeng (Journal of Translational Medicine)
Abstract Background Lung cancer, one of the leading causes of cancer-related morbidity and mortality worldwide, is strongly associated with smoking as its primary carcinogenic factor. However, despite the strong link between smoking and lung cancer, not all smokers develop the disease, suggesting that individual genetic susceptibility and molecular mechanisms may play a critical role in the onset of lung cancer. Understanding the gene-driving mechanisms and immune regulatory pathways involved in smoking-related lung cancer remains one of the key challenges in current lung cancer research. Methods This study employs an integrative bioinformatics approach to explore gene expression differences and immune microenvironment characteristics between smokers with non-small cell lung cancer (NSCLC) and normal individuals. First, smoking-linked lung cancer driver genes (SLDCGs) were identified, followed by Mendelian Randomization (MR) and Summary-based Mendelian Randomization (SMR) analyses to further validate their causal relationships. Next, public databases, including TCGA, GEO, and GTEx, were used to systematically analyze the expression differences of SLDCGs across various clinical subgroups, and immune infiltration analysis was conducted to explore their potential roles in the immune microenvironment of NSCLC. Results The study identified HLA-J and PRMT7 as core driver genes for smoking-associated NSCLC. MR analysis confirmed the potential causal relationship of HLA-J and PRMT7 in the development of NSCLC. Specifically, high expression of PRMT7 was closely associated with the occurrence of NSCLC, while low expression of HLA-J was implicated in immune evasion mechanisms in NSCLC. Additionally, immune microenvironment analysis revealed that HLA-J enhances the activity of immune cells, particularly T cells, to promote tumor immune recognition, whereas PRMT7 suppresses immune cell function, weakening immune surveillance and facilitating immune evasion. Conclusion This study systematically reveals the molecular mechanisms of smoking-linked NSCLC through multidimensional bioinformatics analysis, highlighting the key roles of SLDCGs in immune evasion. The discovery of HLA-J and PRMT7 provides new theoretical foundations for targeted immunotherapy, with significant potential for early diagnosis and personalized treatment of smoking-induced NSCLC. Future research should focus on validating these genes in clinical samples and exploring their potential in immunotherapy.